Modelling the potential public health impact of different vaccination strategies with an omicron-adapted bivalent vaccine in Thailand - Karan Thakkar; Julia Spinardi; Moe H. Kyaw; Jingyan Yang; Carlos Fernando Mendoza; Egemen Ozbilgili; Josie Dodd; Ben Yarnoff; Suda Punrin (Taylor & Francis Group, 2023)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing COVID-19 has continuously evolved, requiring the development of adapted vaccines. This study estimated the impact of the introduction and increased coverage of an Omicron-adapted bivalent booster vaccine in Thailand. Research Design and Methods The outcomes of booster vaccination with an Omicron-adapted bivalent vaccine versus no booster vaccination were estimated using a combined cohort Markov decision tree model. The population was stratified into high- and standard-risk subpopulations. Using age-specific inputs informed by published sources, the model estimated health (case numbers, hospitalizations, and deaths) and economic (medical costs and productivity losses) outcomes in different age and risk subpopulations. Results Booster vaccination in only the elderly and high-risk subpopulation was estimated to avert 97,596 cases 36,578 hospitalizations, 903 deaths, THB 3,119 million in direct medical costs, and THB 10,589 million in indirect medical costs. These benefits increased as vaccination was expanded to other subpopulations. Increasing the booster vaccination coverage to 75% of the standard-risk population averted more deaths (95%), hospitalizations (512%), infections (782%), direct costs (550%), and indirect costs (687%) compared to the base case. Conclusions Broader vaccination with an Omicron-adapted bivalent booster vaccine could have significant public health and economic benefits in Thailand.